TENDENCIES OF MODERN EDUCATION: PROSPECTS FOR EDUCATION REFORMS IN UKRAINE - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The research surveys on the basic tendencies of the education process and prospects for reforms of our country’s education in the 21st century.